Maíz Criollo Negro o Negrito Colombiano (Zea mays L) como alternativa forrajera en el trópico bajo. - Lino Alberto Meza Alba; Dixon Fabian Flórez Delgado; Gladys Montañez Acevedo; Johan Fernando Hoyos Patiño; Dubel Reinaldo Cely Leal (Mundo Fesc)
Background: Colombia, like other countries in Central and South America, has different varieties of native or criollo corn, which are used by indigenous ethnic groups living in remote territories since before the arrival of European settlers. These varieties are used as a source of human food, religious rituals and other purposes other than animal nutrition. Unfortunately, these varieties have been displaced in recent years by improved materials that allow increased grain or biomass production . Objective: This research evaluated the effect of organic and chemical fertilizers on the biomass production of black corn for the production of animal feed. Methods: A complete randomized block was proposed with three treatments and four replications totaling 12 plots of 12 m2 each, where T1 (Urea + DAP) T2 (worm compost) T3 (control). Results: Biomass production of 11.69 kg / ms / m2 was obtained ; 35 g/m2/ m2 in leaves and 55 g/m2/m2 in stem, with an average of 3 ears per plant; a ratio of 14 leaves per stem. Conclusion: There are no significant differences between the application of organic and chemical fertilizers in forage production; this plant material becomes an alternative for obtaining biomass for feeding herbivorous animals in the region and the country.